Prenatal urinary metabolites of polycyclic aromatic hydrocarbons and toddler cognition, language, and behavior. (15th January 2022) - Wallace, Erin R.; Ni, Yu; Loftus, Christine T.; Sullivan, Alexis; Masterson, Erin; Szpiro, Adam A.; Day, Drew B.; Robinson, Morgan; Kannan, Kurunthachalam; Tylavsky, Fran A.; Sathyanarayana, Sheela; Bush, Nicole R.; et al.
Graphical abstract: Highlights: This study examined associations of prenatal PAH and child neurodevelopment. The study population was a large and diverse longitudinal birth cohort. We employed novel methods to examine PAH mixtures and child neurodevelopment. This study is the first to examine differences in PAH effects by prenatal nutrition. We observed some support for adverse associations between PAHs and neurodevelopment. Abstract: Background: Animal and epidemiological studies suggest that prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) may negatively impact toddler neurodevelopment. Methods: We investigated this association in 835 mother–child pairs from CANDLE, a diverse pregnancy cohort in the mid-South region of the U.S. PAH metabolite concentrations were measured in mid-pregnancy maternal urine. Cognitive and Language composite scores at ages 2 and 3 years were derived from the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-3). Behavior Problem and Competence scores at age 2 were derived from the Brief Infant and Toddler Social Emotional Assessment (BITSEA). We used multivariate linear or Poisson regression to estimate associations with continuous scores and relative risks (RR) of neurodevelopment delay or behavior problems per 2-fold increase in PAH, adjusted for maternal health, nutrition, and socioeconomic status. Secondary analyses investigated associations with PAH mixture using Weighted Quantile Sum Regression (WQS) with a permutation test extension. Results: 1- hydroxypyrene was associated with elevated relative risk for Neurodevelopmental Delay at age 2 (RR = 1.20, 95% CI: 1.03, 1.39). Contrary to hypotheses, 1-hydroxynaphthalene was associated with lower risk for Behavior Problems at age 2 (RR = 0.90, 95% CI: 0.83, 0.98), and combined 1- and 9-hydroxyphenanthrene was associated with 0.52-point higher (95% CI: 0.11, 0.93) Cognitive score at age 3. For PAH mixtures, a quintile increase in hydroxy-PAH mixture was associated with lower Language score at age 2 (βwqs = −1.59; 95% CI: −2.84, −0.34; ppermutation  = 0.07) and higher Cognitive score at age 3 (βwqs = 0.96; 95% CI: 0.11, 1.82; ppermutation  = 0.05). All other estimates were consistent with null associations. Conclusion: In this large southern U.S. population we observed some support for adverse associations between PAHs and neurodevelopment.